1991
DOI: 10.1177/096032719101000102
|View full text |Cite
|
Sign up to set email alerts
|

A Histochemical Study of Changes Observed in the Mouse Diaphragm after Organophosphate Poisoning

Abstract: A sublethal dose of sarin (GB, isopropyl methylphosphonofluoridate) was administered to mice. The animals were killed up to 28 d after dosing and frozen sections were made of the excised diaghragms which were stained using haematoxylin and eosin and a modified Gomori trichrome method. Muscle fibre degeneration and mononuclear infiltration were seen, notably at 24 h and 3 d. A number of histochemical procedures were carried out, including the GBHA procedure for ionized calcium. Calcium accumulation, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…High CK level in severely affected subjects were secondary to a direct action with Sarin on skeletal muscles [1,6,8,15,25].…”
Section: Discussionmentioning
confidence: 96%
“…High CK level in severely affected subjects were secondary to a direct action with Sarin on skeletal muscles [1,6,8,15,25].…”
Section: Discussionmentioning
confidence: 96%
“…These authors suggested that hyperstimulation plays a role in myo"ber necrosis. Brigth et al (1991) observed calcium ions next to the neuromuscular junctions in muscle "bers of mice intoxicated with the organophosphate sarin and suggested that accumulation of this ion plays a role in muscle "ber necrosis. Calore et al (1999) reported inhibition of sarcoplasmic esterase and sarcoplamic lipase activity in animals intoxicated with the organophosphate isofenphos.…”
Section: Discussionmentioning
confidence: 98%
“…Os vários autores citados na literatura, que estudaram experimentalmente a miopatia por organofosforados, utilizaram outras técnicas histológicas e histoquímicas, especialmente a coloração pelo tricrômico modificado de Gomori 4,13,14,15,17 . Brigth e col. 3 , 1991, estudaram a expressão da fosfatase ácida em músculos de animais intoxicados, porém sem finalidade de quantificar as lesões.…”
Section: Discussionunclassified
“…Alterações estruturais e funcionais observadas nos músculos esqueléticos estão relacionadas com as estruturas químicas dos produtos e com o tipo de músculo, sendo o diafragma o mais afetado em estudos experimentais 3,4,5,8,9,13,14,15 . Necrose muscular, semelhante à observada em animais de laboratório, foi encontrada em músculos diafragma e intercostais de indivíduos intoxicados pelo parathion 6 , diazinon 1 , triclornato 7 e combinação de malathion e diazinon 18 .…”
Section: Introductionunclassified